Pengaruh Customer Experience, Persepsi Harga dan Kualitas Produk Terhadap Minat Beli Ulang Konsumen Pada CV Prabulinggih Probolinggo - Sania, Nila Alin; Priyono, Achmad Agus; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze and explain the Influence of Customer Experience, Price Perception and Product Quality on Consumers Repurchase Intention at CV Prabulinggih Probolinggo. This research uses a quantitative approach with an associative research type. The sampling technique used is purposive sampling involving 90 respondents who have purchased Prabulinggih Probolinggo batik product. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The research result show that simultaneously customer experience, price perception, and product quality have a significant effect on repurchase intention. Likewise, partially customer experience, price perception, and product quality have a significant effect on repurchase intention. Keywords: Customer Experience, Price Perception, Product Quality, Repurchase Intention.